Evaluation of Phytoremediation Potential of Castor Cultivars for Heavy Metals from Soil - KHAN,M.J. (2019)
ABSTRACT: Phytoremediation is a useful tool to restore heavy metals contaminated soils. This study was carried out to test two castor (Ricinus communis) cultivars [Local and DS-30] for phytoextraction of heavy metals from the soil spiked by known concentrations of seven metals (Cu, Cr, Fe, Mn, Ni, Pb and Zn). A pot experiment was laid out by using a completely randomized design. Soil and plant samples were analyzed at 100 days after planting. The data on heavy metal uptake by plant tissues (roots, leaves and shoots) of the two castor cultivars suggested that a considerable amount of metals (Fe = 27.18 mg L-1; Cu = 5.06 mg L-1; Cr = 2.95 mg L-1; Mn = 0.22 mg L-1; Ni = 4.66 mg L-1; Pb = 3.33 mg L-1; Zn = 15.04 mg L-1) was accumulated in the plant biomass. The soil heavy metal content at the end of experiment significantly decreased with both cultivars, resulting in improved soil quality. Therefore, it is concluded that both castor cultivars, Local and DS-30, can be used for phytoremediation of heavy metal-contaminated sites.